Analyzing Torsion Functions under Robin and Dirichlet Boundary Conditions: Applications and Insights - Hasan, Rizgar Issa (AI Society & STMIK Indonesia, 2024)
In this paper, the author introduces the mathematical concepts regarding torsion functions and their derivations under the Robin and Dirichlet boundary conditions which are integral in mechanical engineering, theoretical physics, and other disciplines. Functions that satisfy given or required partial differential equations contain a wealth of information about materials or structures when subjected to stress. We examine these functions under two types of boundary conditions: Robin, which contains Dirichlet and Neumann conditions, Dirichlet that provides conditions on the boundary. Also, in this section, we formally describe the mathematical model used in the study and provide some definitions, notations, and basic propositions that form the foundation for subsequent analysis. In answer to such concerns, the torsion function problems solved herein utilize analytical and numerical computations to reveal the differences and similarities in behavior between the two boundary conditions. Strong empirical evidence further supports our findings, proving the real-life relevance of the revealed theoretical concepts. Lastly, the implications for these findings in the real-world application are also presented and analysed with regards to advantages and disadvantages of various boundary conditions in the engineering of systems. We end this paper with a presentation of the general implications of the results attained from the work done and possible expansions and directions for future studies as a way of continuing the discourse on the theoretical analysis and actual applications. In summary, this paper provides a useful perspective in the analysis of torsion functions solution under mixed boundary conditions which will be of interest for further development of the theory and application into practice.